Perbedaan Asupan Serat Dan Besar Uang Saku Antara Status Overweight dan Non Overweight Pada Siswa SMK Muhammadiyah 2 Surakarta - Astuty, Ratih Twinda, Eni Purwani S.Si M.Si, dr. Listiana Darmawati M.Si (2016)
Background: prevalence of overweight in vocational high school Muhammadiyah 2 of Surakarta is enough higher until 18.5 %. One factor overweight incidence is poor of intake fibers and money pocket. Lack of intake fibers can risk of diabetes mellitus or coronary heart Objective: This study to know difference intake fiber and money pocket between overweight status and non overweight status of students at vocational high school Muhammadiyah 2 of Surakarta. Method : this research using research observational with cross sectional approach. Collecting data with the measurement anthropometry to know nutritional status of students and food recall in four days not successive to know consumption of fibers and questionnaire of money pocket. taking sample was using proportional random sampling technique and obtained 41 student with overweight nutritional status and 41 student with nonoverweight nutritional status. Analysis data using independent sample test Result : most of overweight subject with fiber intake in category poor ( 51.2 %). The majority of non overweight subjects in enough categories 56.1 %).The majority of overweight subjects have money pocket in enough categories ( 56.1 % ).Most non overweight subjects in enough category (63.4 %). Statistic Test of differences fibers between overweight nutritional status subjects and non overweight subject with p = 0,412. Statistic test of differences money pocket between overweight nutritional status subjects and non overweight subject with p = = 0,185 Conclusions: there is no difference intake fiber and money pocket between overweight status and non overweight status of students at vocational high school muhammadiyah 2 of Surakarta